The effect of neck stabilization exercises in improving of forward head posture in the 20-27 years -old female students - Shohreh taghizadeh; Farahnaz ghafari nejad; Farahnaz emami; Tahereh imani fard; Seiedeh Elham hoseini (Vesnu Publications, 2014)
Introduction: Spinal malalignment is a common problem in the present societies and forward head posture is one of the most common dysfunction in cervical region. The purpose of the present study is to evaluate effect of stabilization exercises in improving of forward head posture. Materials and Methods: Twenty six female students with forward head posture in age range of 20-27 years old participated in this clinical trial study. They were divided in two groups randomly (case and control groups).The land marks of tragus and spinous process of C7 were detected by white markers. The case group did cervical stabilization exercises for 8 weeks. The angle of forward head was measured before and after exercise sessions. Then this angle was compared between two groups. Results: The data revealed that mean difference angle in forward head posture in case group before and after intervention was decreased significantly than control group. (p<0.05) Conclusion: Stabilization exercises are effective in reducing of the angle, therefore it can be useful to improve forward head posture. Key words: forward head posture. Neck stabilization exercises